The Effectiveness of the SKETCH AR Program with Augmented Reality Technology in Developing Creative Thinking for Female Teachers in the Child Education Department (Journal of Hama University, 2022)
The aim of the research was to identify the effectiveness of the SKETCH AR program with augmented reality technology in developing creative thinking among a sample of female teachers in the Department of Child Education (2019-2020). The experimental method was used, through the application of an educational program prepared according to the technology of augmented reality through the Sketcher program, and the creative thinking test for Torrance and Barron, which consisted of twenty phrases. The sample was intended to have a final number of (20) students from the Faculty of Education, Department of Child Education. The results showed the effectiveness of the program in developing creative thinking among the members of the experimental sample. The results also showed that there are statistically significant differences between the mean scores of the members of the experimental sample on the test of creative thinking in the pre and post applications, while there were no differences between the mean scores of the members of the experimental group on the thinking test Creativity in the two-dimensional applications, direct and postponed, indicating that the effect remains in the members of the experimental sample. The researcher suggested increasing interest in creative thinking through the development of programs and activities related to that. She also suggested conducting deeper and more comprehensive field studies on creative thinking and its relationship to other variables.